Temporal Miscoupling: The Challenges and Consequences of Enacting a Practice in Decline - Casillas, Samantha Ortiz; Huising, Ruthanne (Organization Science, 2025)
A practice firmly entrenched in one period can experience decline or even deinstitutionalization in another. However, at the organization level, practice abandonment can be a slow process. Organizations may continue to use a practice that is in decline or out of date, coupling asynchronously with a prior institutional environment. In this paper we develop the concept of temporal miscoupling and examine the challenges of performing a practice under this condition. Drawing on a field study of a labor strike in Canada, we examine the difficulties of inhabiting the practice of striking—picketing a workplace—with eroding political, legal, and cultural support; declining familiarity with the practice; and fading narratives to motivate and justify the practice. We show how strikers developed extemporaneous resources that gave local meaning and form to the practice. These improvised resources supported the practice but distorted historical meanings and performances. Our study expands the analytical repertoire of inhabited institutionalism by problematizing the temporal lag between institutional conditions and organizational practices for the on-the-ground enactment of practices. The extemporaneous resources generated in the context of temporal miscoupling threaten future enactments, indicating an important role for practice enactment in processes of decline and revitalization. Supplemental Material: The online appendix is available at https://doi.org/10.1287/orsc.2021.16026 .